Characterization and Follow-Up of Trypanosoma cruzi Natural Populations Refractory to Etiological Chemotherapy in Oral Chagas Disease Patients - Muñoz-Calderón, Arturo; Díaz-Bello, Zoraida; Alarcón de Noya, Belkisyolé; Noya-González, Oscar O.; Schijman, Alejandro G. (Frontiers in Cellular and Infection Microbiology, 2021)
We aimed to characterize the genetic constitution of natural T. cruzi populations involved in an Oral Chagas Disease (OCD) outbreak at a rural school of the community of Chichiriviche de la Costa, Venezuela, which affected patients did not respond to the etiological treatment. Peripheral blood samples and/or hemocultures were obtained from twenty-nine OCD patients at time of diagnosis or along nine years of Post-treatment (Tx) follow-up. The IgG serology, T. cruzi discrete typing units (DTU), satellite DNA-qPCR parasitic loads, and minicircle signatures were determined at Pre-Tx and after Tx. The serological titles and parasitic loads changed after treatment, with a significant decrease of IgG titers (Spearman’s r value= -0.961) and median parasite loads from 2.869 [IQR = 2.113 to 3.720] to 0.105 [IQR = -1.147 to 1.761] log10 par eq. /mL at Pre-Tx and Post-Tx, respectively, suggesting infection evolution from acute to chronic phase, without seroconversion or parasitological eradication, which was indicative of treatment failure. All patients were infected with T. cruzi DTU I populations. At Pre-Tx their median Jaccard genetic distances were 0.775 [IQR = 0.708 to 0.882], decreasing in genetic variability towards the end of follow-up (Mann-Whitney U test p= 0.0031). Interestingly, no Post-Tx minicircle signature was identical to its Pre-Tx counterpart population in a same patient, revealing selection of parasite subpopulations between the primary infection and Post-Tx. The parasitic populations isolated from hemocultures showed a lower number of bands in the minicircle signatures with respect to the signatures obtained directly from the patients’ blood samples, demonstrating a process of parasitic selection and reduction of the population variability that initially infected the patients. Decrease of parasitic loads after treatment as well as Pre- and Post-Tx intra-TcI diversity might be a consequence of both, natural evolution of the acute infection to the chronic phase and persistence of refractory populations due to Tx selection.